UPAYA PEMBIASAAN BUDAYA RELIGIUS MELALUI KEGIATAN KEAGAMAAN DI SMA ISLAM AL-MA’ARIF SINGOSARI - Nana Nafiri Lathifah; Dwi Fitri Wiyono; Adi Sudrajat (VICRATINA, 2022)
Religious culture is very important to be applied to the school environment. School is a place for students to learn to acquire knowledge and develop various abilities and skills. Religious culture can be practiced in various ways such as discipline, providing honest examples, and creating good habits through religious activities in schools. In this study using a qualitative approach, the authors used the methods of observation, interviews, and documentation. Religious activities at Al-Ma'arif Islamic High School are divided into two structured and unstructured for structured ones, including reading the Qur'an, istighosah, dhuhur and dhuha prayers in congregation, Friday charity etc., for structured activities the implementation of religious activities is carried out every day or once a week which is carried out during class hours and outside class hours. Meanwhile, unstructured religious activities such as PHBI, Pondok Ramadhan, Ubudiyah are held once a year. Supporting factors for habituation of religious culture through religious activities, one of which is very supportive facilities, and a strategic environment, while the inhibiting factors for habituation of religious culture through religious activities at SMA Islam Al-Ma'arif Singosari are the lack of student activity in carrying out religious activities and the lack of sense of solidarity of religious teachers and general field teachers.